The hydrolysis of NO2 dimer in small clusters of sulfuric acid: A potential source of nitrous acid in troposphere. (15th December 2020) - Zhang, Tianlei; Wen, Mingjie; Cao, Xiru; Zhang, Yongqi; Zeng, Zhaopeng; Guo, Ximing; Zhao, Caibin; Lily, Makroni; Wang, Rui
Abstract: Hydrolysis of NO2 dimer is of great interest in atmospheric chemistry because it can form HONO, a major source of OH in polluted urban atmospheres. Herein, the reaction mechanism and kinetics for the hydrolysis of trans -ONONO2 (the favorable route in the hydrolysis of NO2 dimer) catalyzed by catalyst X ( X = H2 SO4, H2 SO4 ⋯ H2 O, and (H2 SO4 )2 ) have been studied theoretically. The calculated results show that the addition of X not only increases the stabilization energy of the reactant complex, but also decreases the energy barrier by over 7.0 kcal⋅mol −1 . Kinetic simulations show that H2 SO4 ⋯ H2 O exerts the strongest catalytic role as compared with H2 SO4, and (H2 SO4 )2 with its pseudo-first-order rate constant k t ′(SW) respectively larger by 6–5 and 10–11 orders of magnitude. Additionally, compared with the rate constant of t -ONONO2 + H2 O reaction, the k t ′(SW) of t -ONONO2 + H2 SO4 ··· (H2 O)2 reaction increase by 13 times at 298 K. Therefore, the present work may suggest that formation of nitrous acid from the hydrolysis reaction of t -N2 O4 is promoted significantly by pre-existing aerosols of small clusters of sulfuric acid. Graphical abstract: Image 1 Highlights: A catalytic effect of H2 SO4, H2 SO4 ⋯ H2 O and (H2 SO4 )2 on the t -ONONO2 + H2 O reaction has been investigated. All of H2 SO4, H2 SO4 ⋯ H2 O and (H2 SO4 )2 catalysts can substantially reduce the energy barriers of the reaction. The H2 SO4 ⋯ H2 O catalyst has the most obvious catalytic effect on the t -ONONO2 + H2 O reaction.